2016
DOI: 10.1186/s40425-016-0189-y
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the dendritic cell-targeting chemokine MIP3α to melanoma antigen Gp100 in a therapeutic DNA vaccine significantly enhances immunogenicity and survival in a mouse melanoma model

Abstract: BackgroundAlthough therapeutic cancer vaccines have been mostly disappointing in the clinic, the advent of novel immunotherapies and the future promise of neoantigen-based therapies have created the need for new vaccine modalities that can easily adapt to current and future developments in cancer immunotherapy. One such novel platform is a DNA vaccine fusing the chemokine Macrophage Inflammatory Protein-3α (MIP-3α) to an antigen, here melanoma antigen gp100. Previous published work has indicated that MIP-3α ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 44 publications
(50 reference statements)
3
46
0
Order By: Relevance
“…Second, inhibition of genes from the repressed component of the program in malignant melanoma cells conferred resistance to CD8 + T cells in a genome-wide CRISPR screen (p =1.67 × 10 −3 , hypergeometric test) (Patel et al, 2017). Third, the program marks the suppression of physical interactions between resistant malignant cells and other cell types in the tumor microenvironment, including MHC I:TCR (T cells), CD58:CD2 (T cells), and IL1RAP:IL1B (macrophages) (Figure 3B and STAR Methods), as well as the senescence-associated secretory phenotype (SASP) (p = 4.3 × 10 −166 and 3.6 × 10 −3 , one-sided t test and mixed effects, respectively; Figure 2D), which has been shown to enhance T cell responses (Gordy et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Second, inhibition of genes from the repressed component of the program in malignant melanoma cells conferred resistance to CD8 + T cells in a genome-wide CRISPR screen (p =1.67 × 10 −3 , hypergeometric test) (Patel et al, 2017). Third, the program marks the suppression of physical interactions between resistant malignant cells and other cell types in the tumor microenvironment, including MHC I:TCR (T cells), CD58:CD2 (T cells), and IL1RAP:IL1B (macrophages) (Figure 3B and STAR Methods), as well as the senescence-associated secretory phenotype (SASP) (p = 4.3 × 10 −166 and 3.6 × 10 −3 , one-sided t test and mixed effects, respectively; Figure 2D), which has been shown to enhance T cell responses (Gordy et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Previous work from our laboratory has shown that the fusion of MIP3α to gp100 enhanced the immunogenicity and efficacy of a DNA vaccine 4 . In the current experiment, a 100 amino acid region of the melanoma-associated antigen tyrosinase-related protein 2 (Trp2) was added to the construct to create a two-antigen vaccine referred to as MIP3α-GpTrp or MGpTrp.…”
Section: Addition Of Trp-2 To Vaccinementioning
confidence: 86%
“…MIP3α is fused to amino acids 25-235 of the human melanoma-associated antigen gp100 proved superior compared to vaccines comprised of defective MIP3α (D-MIP3α) fused to gp100 or MIP3α fused to an irrelevant antigen 4 .…”
Section: A Therapeutic Melanoma Dna Vaccine In Whichmentioning
confidence: 99%
See 1 more Smart Citation
“…116 Transcutaneous genetic vaccination of other melanoma-specific antigens, such as pg100 and MART-1, was also reported to activate T cells or trigger associative recognition after administration by gene guns 117 or eletroporation. 118,119 An enhanced human tyrosinase DNA antigen was designed using a codon-and RNA-optimized approach and it was found to reduce the frequencies of myeloidderived suppressor cells in a syngeneic prophylactic and therapeutic murine model, suggesting a potential strategy for preventing tumor progression and immune escape. 120 Despite the promising results obtained in animal models, it is not easy to evoke sufficient immune responses for significant clinical benefits.…”
Section: Melanoma-specific Antigenmentioning
confidence: 99%